2022
DOI: 10.1021/acsanm.2c02666
|View full text |Cite
|
Sign up to set email alerts
|

Hollow CuO–CeO2 Nanospheres for an Effectively Catalytic Annulation/A3-Coupling Reaction Sequence

Abstract: A heterogeneous catalyst CuO–CeO2 with a hollow structure was successfully synthesized by assembling CuO on the outer surface of CeO2 hollow spheres through a layer-by-layer deposition strategy. Further reduction under a H2 atmosphere was carried out to modify its surface state, resulting in sample r-CuO–CeO2. The catalysts were characterized by X-ray diffraction, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and Fourier transform-infrared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The characteristic peaks at 568.3, 569.0, 570.2 eV in the Auger spectrum of Cu LMM proved the coexistence with Cu + , Cu 2+ and Cu 0 in the sample (Figure 4c). [24] According to previous studies, low valence copper is beneficial to the catalytic coupling reaction, and catalysts with high Cu + /Cu 0 content tend to have better catalytic activity [12] . In Figure 4d, the high‐resolution spectrum of S 2p is divided into four peaks with the corresponding fitting analysis results being presented in Table 1.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…The characteristic peaks at 568.3, 569.0, 570.2 eV in the Auger spectrum of Cu LMM proved the coexistence with Cu + , Cu 2+ and Cu 0 in the sample (Figure 4c). [24] According to previous studies, low valence copper is beneficial to the catalytic coupling reaction, and catalysts with high Cu + /Cu 0 content tend to have better catalytic activity [12] . In Figure 4d, the high‐resolution spectrum of S 2p is divided into four peaks with the corresponding fitting analysis results being presented in Table 1.…”
Section: Resultsmentioning
confidence: 88%
“…The three different morphologies of CuS showed different properties, especially the different content of Cu + /Cu 0 and S n 2− on the surface, which had a powerful effect on the catalytic activity. Previous studies have shown that low valence copper species Cu + /Cu 0 are conducive to the activation of C−H and can promote the reaction [12,27] . S n 2− provides Lewis acid sites, enhances the adsorption of reaction molecules, and is helpful to the cleavage of C−H bonds [28] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations